Mortality trends in a Cohort of Canadian Psoriatic Arthritis Patients - Boluwaji Ogunyemi (McGill University, 2020)
Methods: We reviewed retrospectively the charts of psoriatic arthritis patients who died from 1995-2010.We included 13 deceased patients with a psoriatic arthritis di-agnosis and compared them with 140 patients living with psoriatic arthritis that at-tend the same clinic. The population was derived from a single academic rheumatol-ogist’s practice in St. John’s, Newfoundland, Canada. Patients are seen at six-month intervals with a history and physical exam performed at each visit. Laboratory data was collected at each visit. Diagnosis of psoriatic arthritis is based on the CASPAR Classifcation and Diagnostic Criteria for Psoriatic Arthritis. Results: The mean age of the 13 deceased patients was 62.9 years. Of these, 38.5% were female and 85.7% had an erythrocyte sedimentation rate greater than 15 mm/hour vs. 36.4% of patients living with psoriatic arthritis. Of deceased patients, 16%had dystrophic nail changes of vs. 59.6% of living patients. Health Assessment Questionnaire was found to show a signifcantly greater loss in function in deceasedpatients. (1.39 vs. 0.70, p= 0.002). Almost half of the deceased patients had used Prednisone (46.2%) as opposed to 11.2% of living patients. Conclusions: We realize that this study employs a small sample size. Increased ESR and Health Assessment Questionnaire score were found to be associated with mor-tality in psoriatic arthritis patients. Dystrophic nail changes were found to be pro-tective for psoriatic arthritis patients.